A New Biomarkers Feature Pattern Consisting of TNF-α, IL-10, and IL-8 for Blood Stasis Syndrome with Myocardial Ischemia. (25th November 2013) - Guo, Shuzhen; Chen, Jianxin; Chuo, Wenjing; Liu, Lei; Feng, Xuanchao; Lian, Hongjian; Zheng, Lei; Wang, Yong; Xie, Hua; Luo, Liangtao; Zheng, Chenglong; Fu, Bangze; et al.
Abstract : Objective . To explore new diagnostic patterns for syndromes to overcome the insufficiency of obtainable macrocharacteristics and specific biomarkers. Methods . Chinese miniswines were subjected to Ameroid constrictor, placed around the proximal left anterior descending branch. On the 4th week, macrocharacteristics, coronary angiography, echocardiography, and hemorheology indices were detected for diagnosis. IL-1, IL-6, IL-8, IL-10, TNF- α, and hsCRP in serum were detected, and Decision Tree was built. Results . According to current official-issued standard, model animals matched the diagnosis of blood stasis syndrome with myocardial ischemia based on findings, including >90% occlusion, attenuated left ventricular segmental motion, dark red or purple tongues, and higher blood viscosity. Significant decrease of IL-10 and increase of TNF- α were found in model animals. However, in the Decision Tree, besides IL-10 and TNF- α, IL-8 helped to increase the accuracy of classification to 86%. Conclusions . The Decision Tree building with TNF- α, IL-10, and IL-8 is helpful for the diagnosis of blood stasis syndrome in myocardial ischemia animals. What is more is that our data set up a new path to the differentiation of syndrome by feature patterns consisting of multiple biomarkers not only for animals but also for patients. We believe that it will contribute to the standardization and international application of syndromes.